The anthropometric, physiological, and strength-related determinants of handcycling 15-km time-trial performance - Nevin, J.; Smith, P. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The aim of this study was to investigate the relationship between selected anthropometric, physiological, and upper-body strength measures and 15-km handcycling time-trial (TT) performance. Methods: Thirteen trained H3/H4 male handcyclists performed a 15-km TT, graded exercise test, 15-second all-out sprint, and 1-repetition-maximum assessment of bench press and prone bench pull strength. Relationship between all variables was assessed using a Pearson correlation coefficient matrix with mean TT velocity representing the principal performance outcome. Results: Power at a fixed blood lactate concentration of 4 4 mmol/L (r = .927; P < .01) showed an extremely large correlation with TT performance, whereas relative VO2peak (peak oxygen uptake) (r = .879; P < .01), power-to-mass ratio (r = .879; P < .01), peak aerobic power (r = .851; P < .01), gross mechanical efficiency (r = 733; P < .01), relative prone bench pull strength (r = .770; P = .03) relative bench press strength (r = .703; P = .11), and maximum anaerobic power (r = .678; P = .15) all demonstrated a very large correlation with performance outcomes. Conclusion: Findings of this study indicate that power at a fixed blood lactate concentration of 4 mmol/L, relative VO2peak, power-to-mass ratio, peak aerobic power, gross mechanical efficiency, relative upper-body strength, and maximum anaerobic power are all significant determinants of 15-km TT performance in H3/H4 handcyclists.